Retrospective Evaluation of Cases Undergoing Stereotaxic Brain Biopsy - Yolcu, Abdullah; Akar, Ezgi; Aker, Fügen Vardar; Emon, Selin Tural (Asian Journal of Neurosurgery, 2023)
Objective: The aim of this study is to evaluate the demographic, radiological and histopathological findings, tumoral biomarkers, and survival rates of patients who underwent a stereotactic brain biopsy and those diagnosed with glioblastoma, metastasis, and lymphoma, and the changes in the diagnosis distribution over the years.Materials and Methods: The patients who underwent stereotactic biopsy in our clinic between 2012 and 2020 were evaluated retrospectively. Metastasis, glioblastoma, and lymphoma cases were evaluated as three main groups and the others were excluded. P53 gene expression, isocitrate dehydrogenase (IDH) mutation, and Ki-67 values in glioblastoma cases and Bcl-2, Bcl-6 proteins, and Ki-67 values in lymphomas and their relationship with survival were evaluated.Results: High p53 expression was observed in 27.5% cases diagnosed with glioblastoma. IDH mutation was negative in all glioblastoma cases. Presence of Bcl-2 and Bcl-6 proteins was not associated with survival in lymphomas. Survival rate was significantly higher in cases diagnosed with lymphoma (26.9%) compared to those diagnosed with glioblastoma. A statistically significant increase was determined in patients diagnosed with lymphoma considering the distribution of diseases and incidence and in the distribution of other diagnoses over the years (p < 0.05).Conclusion: As per the distribution of the disease in recent times, it has been observed that there is an increase in lymphoma cases. Histopathology and biomarkers have great importance in the diagnosis and treatment of cerebral lesions. We think that our findings will be supported by studies in which larger patient population and detailed biomarkers will be studied.
Keywords: stereotactic brain biopsy; primary central nervous system lymphomas; glioblastoma; cerebral metastasis